PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYWAN PADA PT. EBEKA MAKMUR ABADI TANGERANG SELATAN - Nur, Khaerudin; Aziz, Abdul (Journal of Research and Publication Innovation, 2024)
By conducting this research, it will be found how the influence of work discipline and work motivation on employee performance at PT. Ebeka Makmur Abadi South Tangerang. Therefore, this research is needed by looking at the hypothesis of how much positive and significant influence between work discipline and work motivation on employee performance. The research method uses quantitative methods with a descriptive approach. The research place was conducted at PT Ebeka Makmur Abadi South Tangerang and the research time was 6 months. The results showed that organizational culture and motivation were in the same strong category. In the Hypothesis test in this study Ho was rejected and Ha was accepted, meaning that Work Discipline and Work Motivation had a significant effect on employee performance at PT. Ebeka Makmur Abadi South Tangerang, and had an influence of 63.4% on Employee Performance. While the remaining 36.6% is influenced by other factors